All at once or one at a time? The effect of simultaneous versus sequential discount presentation on store patronage intentions. Issue 6 (5th February 2020) - DelVecchio, Devon; Wang, Jessie J.; Brigden, Neil
Abstract: Retailers often employ store flyers, be they in print or digital form, to drive store traffic. A fundamental difference in the presentation of multicomponent information, such as the multiple discounts presented in flyers, is whether the components are displayed simultaneously (all at once) of sequentially (one at a time). Yet a little extant research examines how these different presentations affect individuals' responses to retailer price promotions. Three experiments demonstrate that a sequential display of price discounts is associated with more positive store patronage intentions. Evidence, gleaned by both measuring and manipulating the process by which the discounts are evaluated, implicates a greater sense of accumulating benefit with each successive discount when presented sequentially as the driver of the cross‐format difference in patronage intentions.